Effect of annealing on the devitrification behavior and mechanical properties of rapidly quenched Ce-based glassy alloys - Singh D.; Singh D.; Mandal R.K.; Srivastava O.N.; Tiwari R.S. (My University, 2025)
This study deals with the effect of controlled crystallization of melt spun Ce75Al25 − xGax (x = 0, 2, 4 and 6 at.%) and Ce60Cu25Al15 − xGax (x = 0, 1, 2 and 4 at.%) metallic glasses on the formation of nano-composites. It has been found that the substitution of Ga significantly affects the devitrification behavior of these alloys. The Ce75Al25 − xGax alloys with x = 0 shows the formation of hexagonal phase (AlCe3 type) while the alloys with x ≥ 2 give rise to the formation of tetragonal phase (Al2CeGa2 type). Contrary to this, for the Ce60Cu25Al15 − xGax alloys, hexagonal phase of AlCeCu type for x = 0 transforms to hexagonal phase of Al2Cu3Ce type for x ≥ 1. The indentation behavior of nano-composites permitted us to understand the nature of microhardness, yield strength and strain hardening constant. They are compared for the above two alloy systems. The load dependent hardness values of annealed ribbons of Ce75Al19Ga6 and Ce60Cu25Al13Ga2 alloys have been found to be ~ 2.80 GPa and ~ 2.96 GPa, respectively. The absence of cracks around the indentation area up to 200 g of load for Ce60Cu25Al15 − xGax alloys suggests better capability to resist crack propagation in comparison to Ce75Al25 − xGax alloys. Latter display cracks at 200 g load. The formation of shear bands around the periphery of the indenter has been observed. The number of visible shear bands in a given area for the Ce75Al25 − xGax alloys is higher in comparison to those of Ce60Cu25Al15 − xGax alloys. The values of yield strength and Meyer exponent of these alloys are also compared. © 2016 Elsevier B.V.